Shari’ah and ethical issues in the practice of modified Mudharabah family takaful model in Malaysia - Htay, Sheila Nu Nu; Salman, Syed Ahmed (2013)
Takaful has been known as Shari’ah compliant insurance and it is penetrating not only into the Muslim countries but also into the non-Muslim countries. Among the countries which offer Islamic finance products, Malaysia is well known as one of the leading countries encouraging this industry. Due to the rapid growth of the takaful industry, the prevailing guidelines and regulations might not be adequate to capture the current needs of takaful operations. Thus, the practice of takaful industry has been criticized from the Shari’ah and ethical aspects. It is important to examine these main issues because Shari’ah compliance and ethicality are the distinguishing factors that make takaful different from conventional insurance. We also believe that if these issues are not resolved, the participants and the investors will lose the confidence in the takaful industry and consequently, it will hinder the growth of takaful industry. This paper focuses on the Shari’ah and ethical issues in the modified mudarabah model used in family takaful products. They are related to profit (surplus) sharing practice and the usage of interest free loan. The findings of this paper reveal the existence of unfavorable Shari’ah and ethical issues in the practice of takaful operation in Malaysia. Therefore, we suggest that the regulators, Shari’ah advisors and industrial players should revisit on these issues in order to avoid reputational risk, Shari’ah compliant risk and early termination risk.